Está en la página 1de 3

3) 𝑒 𝑥 (𝑦 − 1)𝑑𝑥 + 2(𝑒 𝑥 + 4)𝑑𝑦 = 0

𝑒 𝑥 (𝑦 − 1)𝑑𝑥 = −2(𝑒 𝑥 + 4)𝑑𝑦


𝑒𝑥 𝑑𝑦
− 2(𝑒 𝑥 +4) 𝑑𝑥 = (𝑦−1)

1 𝑒𝑥 𝑑𝑦
− 2 ∫ (𝑒 𝑥 +4) 𝑑𝑥 = ∫ (𝑦−1)

𝑢 = 𝑒𝑥 + 4
𝑑𝑢 = 𝑒 𝑥 𝑑𝑥
Por lo tanto:
1 1 𝑑𝑦
− 2 ∫ 𝑢 𝑑𝑢 = ∫ (𝑦−1)

1
− 2 ln(𝑢) + 𝑐 = ln⁡(𝑦 − 1)
1
− 2 ln(𝑒 𝑥 + 4) + 𝑐 = ln⁡(𝑦 − 1) Respuesta

18) 𝑣(2𝑢𝑣 2 − 3)𝑑𝑢 + (3𝑢2 𝑣 2 − 3𝑢 + 4𝑣)𝑑𝑣 = 0


(2𝑢𝑣 3 − 3𝑣)𝑑𝑢 + (3𝑢2 𝑣 2 − 3𝑢 + 4𝑣)𝑑𝑣 = 0
𝑀 = 2𝑢𝑣 3 − 3𝑣
𝑁 = 3𝑢2 𝑣 2 − 3𝑢 + 4𝑣
𝜕𝑀
= 6𝑢𝑣 2 − 3
𝜕𝑣
𝜕𝑁
= 6𝑢𝑣 2 − 3
𝜕𝑢

𝜕𝑀 𝜕𝑁
= = 𝐸𝑥𝑎𝑐𝑡𝑎
𝜕𝑣 𝜕𝑢

𝑓(𝑢, 𝑣) = ∫(2𝑢𝑣 3 − 3𝑣)𝑑𝑢 = ∫ 2𝑢𝑣 3 𝑑𝑢 − ∫ 3𝑣 𝑑𝑢 = 𝑢2 𝑣 3 − 3𝑢𝑣 + 𝑔(𝑣)


𝑓𝑣 = 3𝑢2 𝑣 2 − 3𝑢 + 𝑔′(𝑣)
3𝑢2 𝑣 2 − 3𝑢 + 𝑔′ (𝑣) = 3𝑢2 𝑣 2 − 3𝑢 + 4𝑣
𝑔′ (𝑣) = 4𝑣
𝑔(𝑣) = 2𝑣 2 + 𝑐
Por lo tanto:
𝑓(𝑢, 𝑣) = 𝑢2 𝑣 3 − 3𝑢𝑣 + 2𝑣 2 + 𝑐
𝑢2 𝑣 3 − 3𝑢𝑣 + 2𝑣 2 = 𝑐 Respuesta

33) (2𝑦 3 − 𝑥 3 )𝑑𝑥 + 3𝑥𝑦 2 𝑑𝑦 = 0 => 𝐻𝑜𝑚𝑜𝑔é𝑛𝑒𝑎⁡𝑑𝑒⁡3𝑒𝑟⁡𝑔𝑟𝑎𝑑𝑜


𝑦 = 𝑣𝑥 𝑑𝑦 = 𝑣𝑑𝑥 + 𝑥𝑑𝑣
(2𝑣 3 𝑥 3 − 𝑥 3 )𝑑𝑥 + 3𝑣 2 𝑥 3 (𝑣𝑑𝑥 + 𝑥𝑑𝑣) = 0
𝑥 3 (2𝑣 3 − 1)𝑑𝑥 + 𝑥 3 (3𝑣 3 𝑑𝑥 + 3𝑣 2 𝑥𝑑𝑣) = 0
(2𝑣 3 − 1)𝑑𝑥 + 3𝑣 3 𝑑𝑥 + 3𝑣 2 𝑥𝑑𝑣 = 0
(5𝑣 3 − 1)𝑑𝑥 + 3𝑣 2 𝑥𝑑𝑣 = 0
(5𝑣 3 − 1)𝑑𝑥 = −3𝑣 2 𝑥𝑑𝑣
𝑑𝑥 3𝑣 2
− = (5𝑣3 −1) 𝑑𝑣
𝑥

𝑑𝑥 3𝑣 2
−∫ = ∫ (5𝑣3 −1) 𝑑𝑣
𝑥

𝑑𝑥 1 15𝑣 2
−∫ = 5 ∫ (5𝑣3 −1) 𝑑𝑣
𝑥

𝑤 = 5𝑣 3 − 1
𝑑𝑤 = 15𝑣 2 𝑑𝑥
Por lo tanto:
𝑑𝑥 1 𝑑𝑤
−∫ = 5∫
𝑥 𝑤
1
− ln(𝑥) + 𝑐 = 5 ln⁡(𝑤)
1
− ln(𝑥) + 𝑐 = 5 ln⁡(5𝑣 3 − 1) Respuesta

48) 𝑦(𝑥 2 + 𝑦 2 )𝑑𝑥 + 𝑥(3𝑥 2 − 5𝑦 2 )𝑑𝑦 = 0 => 𝐻𝑜𝑚𝑜𝑔é𝑛𝑒𝑎⁡𝑑𝑒⁡3𝑒𝑟⁡𝑔𝑟𝑎𝑑𝑜


𝑦 = 𝑣𝑥 𝑑𝑦 = 𝑣𝑑𝑥 + 𝑥𝑑𝑣
(𝑣𝑥 3 + 𝑣 3 𝑥 3 )𝑑𝑥 + (3𝑥 3 − 5𝑣 2 𝑥 3 )(𝑣𝑑𝑥 + 𝑥𝑑𝑣) = 0
𝑥 3 (𝑣 + 𝑣 3 )𝑑𝑥 + 𝑥 3 (3𝑣𝑑𝑥 + 3𝑥𝑑𝑣 − 5𝑣 3 𝑑𝑥 − 5𝑣 2 𝑥𝑑𝑣) = 0
(𝑣 + 𝑣 3 )𝑑𝑥 + 3𝑣𝑑𝑥 + 3𝑥𝑑𝑣 − 5𝑣 3 𝑑𝑥 − 5𝑣 2 𝑥𝑑𝑣 = 0
(4𝑣 − 4𝑣 3 )𝑑𝑥 + 𝑥(3 − 5𝑣 2 )𝑑𝑣 = 0
𝑑𝑥 (3−5𝑣 2 )
− = (4𝑣−4𝑣3 ) 𝑑𝑣
𝑥

𝑑𝑥 (3−5𝑣 2 )
−∫ = ∫ (4𝑣−4𝑣3 ) 𝑑𝑣
𝑥

𝑑𝑥 1 (5𝑣 2 −3)
−∫ = 4 ∫ 𝑣(𝑣2 +1) 𝑑𝑣
𝑥

𝑑𝑥 1 (5𝑣 2 −3)
−∫ = 4 ∫ 𝑣(𝑣+1)(𝑣−1) 𝑑𝑣
𝑥

Por fracciones parciales:


𝑑𝑥 1 3 1 1 1 1
−∫ = 4 ∫ 𝑣 𝑑𝑣 + 4 ∫ 𝑣+1 𝑑𝑣 + 4 ∫ 𝑣−1 𝑑𝑣
𝑥
3 1 1
− ln(𝑥) + 𝑐 = 4 ln(𝑣) + 4 ln(𝑣 + 1) + 4 ln⁡(𝑣 − 1) Respuesta

63) (𝐷3 + 𝐷2 − 16𝐷 − 16)𝑦 = 0


𝑚3 + 𝑚2 − 16𝑚 − 16 = 0
Obteniendo las raíces del polinomio:
𝑚1 = −4
𝑚2 = −1
𝑚3 = 4
𝑦𝐻 = 𝐶1 𝑒 −4𝑥 + 𝐶2 𝑒 −𝑥 + 𝐶3 𝑒 4𝑥 Respuesta